Electrochemical reduction and capacitance of hybrid titanium dioxides—nanotube arrays and "nanograss". (20th August 2016) - Du, Kang; Liu, Guohua; Li, Mengwei; Wu, Chenggen; Chen, Xuyuan; Wang, Kaiying
Abstract: In this paper, we report enhanced electrochemical capacitance of well-aligned TiO2 nanotube arrays with "nanograss" synthesized by electrochemical anodization. The conductivity of hybrid materials is improved by electrochemical reduction method, exhibiting an outstanding specific capacitance of 14.3 mF cm −2, which is 14 times larger than pristine ones. The specific capacitance further increases up to 20.5 mF cm −2, which is 43.4% higher than reduced ones with selectively retention of "nanograss" by ultrasonic treatment. We expect that the electrochemical-reduction approach and controllable morphology modification offer a potential path for developing high-performance energy storage devices.